2002
DOI: 10.1061/(asce)0887-3801(2002)16:2(143)
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Algorithm for Solving Site Layout Problem with Unequal-Size and Constrained Facilities

Abstract: This paper presents an investigation of the applicability of a genetic approach for solving the construction site layout problem. This problem involves coordinating the use of limited site space to accommodate temporary facilities so that transportation cost of materials is minimized. The layout problem considered in this paper is characterized by affinity weights used to model transportation costs between facilities and by geometric constraints that limit their relative positions on site. The proposed genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 12 publications
0
37
0
2
Order By: Relevance
“…The function is total cost as a sum of the product of Hook Travel Time [7], quantity of material flow and cost of material flow from Source to Destination per unit quantity and unit time. Genetic algorithms were used in several studies to optimize the layouts of construction sites [6,[8][9][10][11]. These genetic algorithms have shown improvements in the search process for near optimal solutions, especially in this type of problem that is characterized by a large search space.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The function is total cost as a sum of the product of Hook Travel Time [7], quantity of material flow and cost of material flow from Source to Destination per unit quantity and unit time. Genetic algorithms were used in several studies to optimize the layouts of construction sites [6,[8][9][10][11]. These genetic algorithms have shown improvements in the search process for near optimal solutions, especially in this type of problem that is characterized by a large search space.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Later, El-Baz [29] compared the effectiveness of his GA solution with Chan & Tansri's [27] and Mak et al's solution [28] and showed that, for the same tests, it performs better. Zouein et al [30] used GA to solve the site layout problem, characterized by affinity weights and 2D geometric constraints between facilities. Jang et al [31] applied GA for multi-floor layout problems, considering both horizontal and vertical material handling.…”
Section: B Resolution Approachesmentioning
confidence: 99%
“…The available literature on site layout focus mainly on optimising the locations of temporary facilities through addressing objectives such as travel cost, material handling cost, safety breaches and wildlife preservation [16]- [21]. Literature addressing noise levels on construction sites mostly emphasise the quantification of the sound levels produced.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%